Efficacy and safety of azilsartan medoxomil, an angiotensin receptor blocker, in Korean patients with essential hypertension - Attila Juhasz; Jingtao Wu; Michie Hisada; Tomoka Tsukada; Myung Ho Jeong (BMC, 2018)
Abstract Background This was a phase 3, randomized, double-blind, placebo-controlled study. Methods Adult Korean patients with essential hypertension and a baseline mean sitting clinic systolic blood pressure (scSBP) ≥150 and ≤180 mmHg were randomized to 6-week treatment with placebo (n = 65), azilsartan medoxomil (AZL-M) 40 mg (n = 132), or AZL-M 80 mg (n = 131). The primary endpoint was the change from baseline to week 6 in trough scSBP. Results The least-squares mean (standard error) change from baseline in trough scSBP in the placebo, AZL-M 40-mg, and 80-mg groups at week 6 were − 8.8 (2.00), − 22.1 (1.41), and − 23.7 (1.40) mmHg, respectively (p < 0.001 for AZL-M 40 and 80 mg vs placebo). No clinically meaningful heterogeneity in efficacy was observed between subgroups (age, sex, diabetes status) and the overall population. Treatments were well tolerated and adverse events were similar between groups. Conclusions Results of this study confirm a positive benefit-risk profile of AZL-M for essential hypertension in Korean adults. Trial registration Clinicaltrial.gov; identifier number: NCT02203916. Registered July 28, 2014 (retrospectively registered)